THE USE OF ACTIVE LEARNING METHODS IN LEARNING FIQH SUBJECTAT ISLAMIC BOARDING SCHOOL - Firman Mansir; Tumin Tumin; Halim Purnomo (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract:This study discussed about the use of active learning methods in Fiqh learning in Islamic Boarding School. This research used qualitative approach by collecting data through library research. The primary data was articles about active learning methods. Data collection procedures were carried out by collecting various books, articles, theses, and dissertations that discussed about Fiqh subject and Islamic education in Islamic boarding school (pesantren). Research data were analyzed through deductive and inductive process. The result indicated that Active Learning method could be used to teach Fiqh subject in the Islamic Boarding School. The material taught should be appropriated with the Active Learning Method used. By using active learning method, it was expected that the students of Islamic boarding school were engaged, motivated, and interested to learn Fiqh subject.Abstrak:Penelitian ini membahas tentang penggunaan metode pembelajaran aktif dalam pembelajaran Fiqh di Pondok Pesantren. Penelitian ini menggunakan pendekatan kualitatif dengan mengumpulkan data melalui penelitian kepustakaan. Data primer adalah artikel tentang metode pembelajaran aktif. Prosedur pengumpulan data dilakukan dengan mengumpulkan berbagai buku, artikel, tesis, dan disertasi yang membahas tentang mata pelajaran Fiqh dan pendidikan Islam di pondok pesantren. Data penelitian dianalisis melalui proses deduktif dan induktif. Hasil penelitian menunjukkan bahwa metode Pembelajaran Aktif dapat digunakan untuk mengajar mata pelajaran Fiqh di Pondok Pesantren. Materi yang diajarkan harus disesuaikan dengan Metode Pembelajaran Aktif yang digunakan. Dengan menggunakan metode pembelajaran aktif, diharapkan para siswa pondok pesantren terlibat, termotivasi, dan tertarik untuk belajar mata pelajaran Fiqh.